Climate Damage Functions for Estimating the Economic Impacts of Climate Change in the United States. (9th January 2020) - Neumann, James E; Willwerth, Jacqueline; Martinich, Jeremy; McFarland, James; Sarofim, Marcus C; Yohe, Gary
Abstract: Recent advancements in the availability of models and data to characterize the economic impacts of climate change have improved our ability to project both the physical impacts and economic effects of climate change across economic sectors of the United States. These advancements have in turn provided an opportunity to estimate these impacts across multiple economic sectors using a consistent set of damage functions. These functions can be used to inform decision making regarding the diversity and magnitude of future impacts and how adaptation and other actions can affect the risk of economic impacts. This article shows how damage functions can be developed from the results of detailed modeling studies and then used to estimate future economic impacts. We estimate damage functions based on 15 sectoral impact models that project the economic impacts of climate change on human health, infrastructure, and ecosystems and, with a focus on temperature, apply these functions to changes in economic impacts for seven U.S. regions through 2100. We also discuss the uncertainty of these results. We conclude that, although further research is needed, the methods presented here can be usefully applied to a range of alternative temperature trajectories to estimate the economic effects of climate change.